Analysis of non‐severe acute onset autoimmune hepatitis according to the presence of radiological heterogeneity. Issue 9 (11th June 2022) - Fujiwara, Keiichi; Fukuda, Yoshihiro; Seza, Katsushi; Saito, Masaya; Koizumi, Shuko; Yokosuka, Osamu; Kato, Naoya
Abstract: Aim: Diagnosis of acute onset autoimmune hepatitis (A‐AIH) has been difficult in that patients may not have typical clinicopathological features of AIH. In our previous reports of severe and fulminant AIH, two‐thirds of them showed radiological heterogeneity: hepatic heterogeneous hypoattenuation on unenhanced computed tomography (CT) reflecting heterogeneous distribution of massive hepatic necrosis (severe centrilobular necrosis), which would be beneficial for the diagnosis. In the present study, we analyzed non‐severe A‐AIH patients with or without radiological heterogeneity and tried to find novel clinical features for supporting the early diagnosis. Methods: Clinical, biochemical, immunological, radiological and histological features of 42 patients with non‐severe A‐AIH at community hospitals between 2010 and 2020 were analyzed. Results: Of 42, 28 patients on whom CT scans were performed and who could be fully analyzed were enrolled. Five patients showed hepatic heterogeneous hypoattenuation on unenhanced CT. There was no significant difference in clinical, biochemical, immunological and histological features at diagnosis between the two groups according to the presence of radiological heterogeneity, although mean minimum prothrombin time activity during the course was lower in patients with heterogeneity without statistical significance ( p  = 0.080). All responded to treatment well and achieved initial remission within 3 months. Conclusions: It is possible that patients with non‐severe A‐AIH show radiological heterogeneity reflecting centrilobular necrosis which is one of important diagnostic features of A‐AIH. Accordingly, radiological heterogeneity might be beneficial for the diagnosis of A‐AIH in combination with conventional clinicopathological features if it is detected in the absence of features suggestive of other liver diseases.